2019
DOI: 10.1155/2019/5232308
|View full text |Cite
|
Sign up to set email alerts
|

A Vitamin Pattern Diet Is Associated with Decreased Risk of Gestational Diabetes Mellitus in Chinese Women: Results from a Case Control Study in Taiyuan, China

Abstract: Identification of modifiable dietary factors, which are involved in the development of gestational diabetes mellitus (GDM), could inform strategies to prevent GDM. Therefore, we examined the dietary nutrient patterns and evaluated their relationship with GDM risk in a Chinese population using a case control study design. A total of 1,464 GDM cases and 8,092 non-GDM controls were included in the final analysis. Dietary intake was assessed using a 33-item food frequency questionnaire, and nutrients were estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 35 publications
4
22
0
Order By: Relevance
“…According to a systematic review and meta-analysis of longitudinal or cohort studies with 30,871 pregnant women, diets such as Mediterranean Diet (MedDiet), Dietary Approaches to Stop Hypertension (DASH) diet and Alternate Healthy Eating Index diet (AHEI) were associated with 15–38% reduced relative risk of GDM [ 44 ]. A case-control study conducted in Taiyuan, China reported that a vitamin pattern diet (characterized as consumption of diet rich in vitamin A, carotene, vitamin B2, vitamin B6, vitamin C, dietary fiber, folate, calcium, and potassium) is associated with decreased risk of GDM in Chinese women [ 70 ]. Evidence from the Chinese Prospective Birth Cohort Study showed that dietary pattern with high vegetable, fruit, and rice intake was associated with a lower GDM risk among Chinese pregnant women [ 45 ].…”
Section: Prevention and Lifestyle Intervention Of Gdm In Chinamentioning
confidence: 99%
“…According to a systematic review and meta-analysis of longitudinal or cohort studies with 30,871 pregnant women, diets such as Mediterranean Diet (MedDiet), Dietary Approaches to Stop Hypertension (DASH) diet and Alternate Healthy Eating Index diet (AHEI) were associated with 15–38% reduced relative risk of GDM [ 44 ]. A case-control study conducted in Taiyuan, China reported that a vitamin pattern diet (characterized as consumption of diet rich in vitamin A, carotene, vitamin B2, vitamin B6, vitamin C, dietary fiber, folate, calcium, and potassium) is associated with decreased risk of GDM in Chinese women [ 70 ]. Evidence from the Chinese Prospective Birth Cohort Study showed that dietary pattern with high vegetable, fruit, and rice intake was associated with a lower GDM risk among Chinese pregnant women [ 45 ].…”
Section: Prevention and Lifestyle Intervention Of Gdm In Chinamentioning
confidence: 99%
“…7 were cohort [13] [23], one had a case-control design [24] and only one was an interventional randomized controlled trial (RCT) [23]. 8 studies were conducted in China [13] [17] [19]- [24], and only one in USA [25]. All studies were published and written in English.…”
Section: Search Resultsmentioning
confidence: 99%
“…The eligible studies included a minimum of 326 pregnant women [14] and a maximum of 20,199 [25] with a mean of 5626 participants. Participants were diagnosed to have GDM based on different validated criteria: National diabetes data group and 3 rd International workshop conference [25], Carpenter Coustan [19] [24], International association of diabetes and pregnancy study groups […”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a clear role for an optimal diet both before and during pregnancy to support the health of the mother and offspring [ 8 , 9 , 10 , 11 , 12 ]. Higher dietary scores for a high-protein/fruit pattern before pregnancy, was associated with decreased likelihood of preterm birth (adjusted odds ratio; 95% confidence interval, OR: 0.31; 95% CI: 0.13, 0.72), whereas the reverse direction was apparent for the high-fat/sugar/takeaway pattern (adjusted OR: 1.54; 95% CI: 1.10, 2.15) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%